Influencing factors of suicide in hospitalized patients with mental disorders: a retrospective study using medical malpractice cases in China - Qiang Wang; Daming Sun; Guangjian Li; Lin Li; Hongyan Li; Yajun Xu (Frontiers in Psychiatry)
ObjectiveThis study aims to reveal the suicide risk factors in specific situations of medical malpractice.MethodsWe conducted a systematic analysis using the medical malpractice case data from the judgment search system on China Judgments Online, covering the years 2012 to 2022. The χ2 test was applied to compare group differences, while a binary logistics regression analysis was used to assess factors influencing suicide among hospitalized patients with mental disorders.ResultsA total of 268 finalized medical malpractice judgments were analyzed. From 2012 to 2022, medical malpractice cases involving psychiatric inpatients in China show a significant upward trend. Suicide cases of hospitalized patients with mental disorders accounted for 32.5% of all medical malpractice cases. These incidents were more frequent in comprehensive hospitals, tertiary hospitals, and economically developed regions such as East China and Central China. Chi-square testing and multivariate binary logistic regression analysis revealed that hospital type, history of suicidal behavior, clinical psychiatric diagnosis of others, medical fault in violating specific regulations, and medical fault in breach of duty of care were identified as independent risk factors (OR=2.662,3.866,3.567,3.247,3.593; 95% CI: 1.368-5.180, 1.473-10.146, 0.398-9.107,1.193-8.838,1.406-9.179).ConclusionsIn China, the proportion of suicide cases of hospitalized psychiatric patients in civil cases of medical malpractices has been increasing. Independent risk factors include hospital type, suicidal history, history of suicidal behavior, clinical psychiatric diagnosis of others, medical fault in violating specific regulations and medical fault in breach of duty of care. Optimizing resource allocation in comprehensive hospitals, enhancing ward safety, and standardizing clinical protocols are urgently needed to mitigate preventable suicides in this vulnerable population.